PARTISIPASI REMAJA DALAM PROGRAM DAKWAH DI MASJID NURUL YAQIN KELURAHAN MALENI KABUPATEN DONGGALA - nurmiati; Ahmad Said Al-Anshari (Sambulu Gana : Jurnal Pengabdian Masyarakat, 2025)
This research aims to analyze youth participation in the da'wah program at the Nurul Yaqin Mosque, Maleni Village, Donggala Regency. Youth participation is very important in the religious and social development of society. In the context of mosques, teenagers have a strategic role in supporting da'wah activities to make them more dynamic and sustainable. The research method used is qualitative with a descriptive approach. Data was collected through observation, interviews and documentation. The research results show that the level of youth participation at the Nurul Yaqin Mosque is still relatively moderate. Factors that influence participation include family support, social environment, and the attractiveness of the da'wah program being held. Obstacles faced include a lack of internal motivation among teenagers, a lack of innovation in delivering preaching material, and limited supporting facilities. This research suggests improving the quality of da'wah programs by involving more creative and modern elements to make them more relevant to the needs and interests of today's teenagers.